2017
DOI: 10.1002/jcla.22154
|View full text |Cite
|
Sign up to set email alerts
|

Status of internal quality control for thyroid hormones immunoassays from 2011 to 2016 in China

Abstract: With change of IQC practice, only FT3 had precision performance improved in 6 years. However, precision status of five analytes in China was still unsatisfying. Ongoing investigation and improvement of IQC have yet to be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Similar findings for FT4 Immulite 2000 assay were declared by Hendriks et al [7]. A recent Chinese study revealed lower precision rates for several FT4 assays compared to precision performance of TSH assays on different analytical platforms [20].…”
Section: Discussionsupporting
confidence: 85%
“…Similar findings for FT4 Immulite 2000 assay were declared by Hendriks et al [7]. A recent Chinese study revealed lower precision rates for several FT4 assays compared to precision performance of TSH assays on different analytical platforms [20].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the Westgard Sigma rule, the total number of control measurements per QC event (N), and the run size of patient samples between two adjacent QC events (R) per day were also introduced in the SQC procedure of all the analytes. The selection of QC procedure is vital in balancing appropriate Pfr and Ped scores for the analytes as well as avoiding economic costs and overwork 29. For instance, based on the re-evaluated sigma values of FT3, TT3, TSH, CROT, E2, LH, and F I G U R E 3 The effects of analytical temperature and humidity on the performance of analytes evaluated with sigma metrics (Level 1 and Level 2) by the same staff.…”
mentioning
confidence: 99%
“…In a study concerning performances of four analytical platforms that use CLIA or ECLIA technology in an external quality assessment program over five years, only 50% of the evaluated laboratories met the desired quality performances. In all cases, CV% values were below the desired value of 9.6% (8).…”
Section: Discussionmentioning
confidence: 68%